Daughter of the morning star [large type] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery, 2022)
"When Lolo Long's niece Jaya begins receiving death threats, Tribal Police Chief Long calls on Absaroka County Sheriff Walt Longmire along with Henry Standing Bear as lethal backup. Jaya "Longshot" Long is the phenom of the Lame Deer Lady Stars High School basketball team and is following in the steps of her older sister, who disappeared a year previously, a victim of the scourge of missing Native Woman in Indian Country. Lolo hopes that having Longmire involved might draw some public attention to the girl's plight, but with this maneuver she also inadvertently places the good sheriff in a one-on-one with the deadliest adversary he has ever faced in both this world and the next"-- Provided by publisher.